Slotted log periodic antenna with first iteration Fractal Koch technique for UHF TVWS applications - Rahman, N. A. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper proposed a compact Log Periodic Fractal Koch Antenna (LPFKA) by utilizing slots for Ultra High Frequency (UHF) Television White Space Spectrum (TVWS) bands applications. This log periodic antenna is comprised of ten radiating elements with titled slot angles and placed on both sides of the substrate in crisscross arrangement. This antenna was designed at frequency between 0.47 GHz and 0.79 GHz which focus on UHF TVWS bands. With the gains from 4.41 dBi to 7.2 dBi and reflection coefficient below than -10 dB over desired frequencies, this antenna is suitable and has a big potential for super Wi-Fi UHF TVWS applications.